Influence of Bacau City’s Anthropic Activities on the Heavy Metals Concentration Measured on Bistrita and Siret River Sides (London Journal of Research In Science: Natural and Formal, 2025)
The main objective of the current research is to determine the content of heavy metals from the Bistrita and Siret River banks, respectively Siret River in Bridge Holt area, Siret River canal UHE and Siret River- downstream confluence Bistrita/Siret. The choice of sampling points took into consideration the areas where the pollution sources are located. Established maximum values were not exceeded in the case of mercury in the soil for all three sampling points Siret River in Bridge Holt area, Siret River canal UHE and Siret River- downstream confluence Bistrita/Siret. Exceeding values recorded in the sampling points Siret River in Bridge Holt area, Siret River canal UHE and Siret River- downstream confluence Bistrita/Siret (for cadmium, nickel and chrome) resulted from discharged residual waters, industrial platforms form Bacau city and the improper storage of municipal waste.
Keywords: pollution; Soil; heavy metals; Siret River sides